(untitled) (Forum Theologicum Sardicense, 2025)
Ivan Christov, Byzantine Synaxaristes for September. The present publication of the prologue verses for September is the first part of a larger project that includes the verses for the entire year. Our aim is to provide as wide a range of sources as possible. We introduce into modern research four Greek MSS, stored in the Ecclesiastic-historical and Archival Institute at the Bulgarian Patriarchate in Sofia – three from 14th century (EHAI 830, 384 и 217) and one from the 16th century (EHAI 398). These manuscripts are used for comparison and to complement the sources of the existing editions of S. Eustratiadis, E. Follieri and D.Z. Sofianos. Vitae in verses that are absent in these editions, such as those of Theodora (11.IX) and Euphrosyne (25.IX) are published from the MSS. A significant part of the work on the Greek text and the Bulgarian translation was conducted in the Ostkirchliches Institut in Regensburg in 2011. We hope that the present publication will contribute to further research on the synaxarium metricum and its Slavonic reception.